A REVIEW: AQUILARIA SPECIES AS POTENTIAL OF PHARMACOLOGICAL - Nelly Marliani (OISAA, 2021)
One of the plants that is rich in benefits is from the genus Aquilaria spp. which is known to be able to produce agarwood resin. This genus includes 47 species, of which the four main species are Aquilaria malaccensis, Aquilaria subintegra, Aquilaria crassna and Aquilaria sinensis. Aquilaria species are known to have a wide spectrum of pharmacological activity and have been reported in many studies, including activity, anticancer, anti-inflammatory, AChE inhibitor (Acetylcholinesterase), anti-proliferative, and antidiabetic. The aim of this review is to expand information on the pharmacological activity of various Aquilaria species that can support future studies in the medical field of medicine.